Interacting labour force and Human Capital Development Effects on Manufacturing Sector Productivity - Babasanya, Adeyemi Olayiwola; Okuneye, Babatunde Adekunle; Amaefule, Joseph Nwabueze (ETIKONOMI, 2025)
Research Originality: The adoption of technology in the industrial world requires a high-quality workforce. This research provides a novelty by testing human capital development against the output of the manufacturing industry.Research Objectives: This study analyzes the interactive impact of the industrial labor force and human capital development on manufacturing sector output in the West African Sub-Region from 1989 to 2022.Research Methods: The study adopted an ex post facto research design. The data used for analysis was sourced from the World Development Indicator (WDI), and the Panel ARDL method was employed to investigate the interactive impact of industrial labor force and human capital development on manufacturing output..Empirical Results: The results suggest that labor force and human capital had an interactive negative, insignificant impact on manufacturing output in the short run, while in the long run, the interaction of labor force and human capital had a significant favorable influence on the manufacturing sector's output. The composite human capital index had no significant impact on output in the manufacturing sector in both the short run and the long run.Implications: Policymakers should focus on developing initiatives that will enhance the labor force's skill sets and align them with the needs of the manufacturing sector.JEL Classification: J21, O14, O55How to Cite:Babasanya, A. O., Okuneye, B. A., & Amaefule, J. N. (2025). Interacting Labor Force and Human Capital Development Effects on Manufacturing Sector Productivity. Etikonomi, 24(1), 221 – 232. https://doi.org/10.15408/etk.v24i1.38648.